Investigando a experiência da fruição do futebol : estádio versus televisão - Carauta, Alexandre Augusto Freire (2008)
This work aims to investigate the spectator narratives associated with live football and TV football broadcasting. Long interviews (McCracken, 1988) were conducted with 16 subjects, focusing on their personal history and experienced narratives are related to life and sports practice and consumption. Interviews were focused on subjects experiences with live and TV football watching experiences. The conceptual framework provided by Holbrook (1999) was used to identify consumer behavior; to describe the different forms of fruition and evaluation. Observations points to active participation in message building on the pitch with high leveIs of connotative content, contrasting with high denotative content on the TV messages, which stresses the didactical character of TV broadcastings. As the forms of presentation of the football spectacle can be seen as packets of information, we can bring to this analysis the ideas of Eco (2001). For Eco, the value of information is proportional to the richness of choices and possible meanings. Such approach is consistent with the proposition by Holbrook (1999) that the valuation of consumption experience is derived from interaction with the world. This way, the degree of interactivity is directly related to the volume of associative connotations preceded by the spectator.